Budaya Religius Sekolah Sebagai Upaya Membentuk Kecerdasan Emosional Siswa di Man 4 Jombang - Niswah Qonitah (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2020)
Education in Indonesia at the moment seems to be oriented towards cognitive intelligence alone. So many problems arise character degradation. This is because education in Indonesia is still lacking in developing student’s emotional intelligence. Recognizing this reality, there needs to be concrete and sustainable solutions. In this case the religious culture of schools can be used as a tool to realize the character building of students. Therefore, the purpose of this study is to describe the form of school religious culture, and analyze the contribution of school religious culture to students' emotional intelligence. This research is a type of qualitative research. The results showed that the form of school religious culture at MAN 4 Jombang consisted of 3 implementations namely a) daily activities such as prayer before and after the lesson. b) weekly activities consisting of istighosah, khitobah, and social funding programs. c) annual activities carried out to commemorate Islamic holidays (PHBI) consisting of isra’ mi'raj, Eid al-Adha commemoration, and national santri day. While the contribution of the schools religious culture as an effort to shape students emotional intelligence consists of a) istighosah can shape managing emotions, b) the khitobah can shape students' self-motivation, c) social fundraising can shape student empathy, d) PHBI can form fostering relationships, and e ) overall religious cultural activities are able to bring out the student’s self-awareness. Keywords: School Religious Culture, Emotional Intelligence